Online Learning Strategies amid New Normal Era in Indonesia - Ida Bagus Nyoman Mantra; Nengah Dwi Handayani; Anak Agung Istri Yudhi Pramawati (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Many aspects of life have to be reorganized as an impact of the Covid-19 pandemic. The application of physical distancing for the world of education forced the learning activities to be conducted through online systems. In the beginning, online learning was a highly difficult challenge for most educators, because they were unfamiliar with online learning and some of them were doubtful about the effectiveness of online learning. Consequently, many teachers implemented whatever learning strategies they thought to be effective to improve students’ learning achievement. This study explored effective learning strategies used by educators in Indonesia during the new normal era of Covid-19. This study used a mixed-method research design, and the data were collected by using a questionnaire and interviews. 216 respondents participated in this study consisting of university lecturers and schoolteachers. The collected data were then critically analysed, and the findings were described descriptively. This study revealed that educators mostly used online learning, blended learning, project-based learning, and limited face-to-face learning to continually enhance students’ learning competence. This study implies that teachers should creatively develop the existing teaching strategies to suit students’ learning conditions.